Retrosigmoid Craniotomy for Cerebellopontine Epidermoid Cyst - Höhne, Julius (J Neurol Surg B Skull Base, 2019)
Epidermoid cysts are benign lesions. The goal of this surgery is complete removal while preserving cranial nerves. Here, we illustrate the case of a 31-year-old male who presented with persistent headache following a short period of impaired consciousness. Imaging revealed a mass at the cerebellopontine angle (CPA) which at surgery proved to be an epidermoid cyst. In this video, we present the key steps of surgery. The postoperative course was uneventful and the patient was symptom-free at the 3 months of follow-up. The link to the video can be found at: https://youtu.be/0xwpkKwQoLI .